Fast femtosecond laser ablation for efficient cutting of sintered alumina substrates. (September 2016) - Oosterbeek, Reece N.; Ward, Thomas; Ashforth, Simon; Bodley, Owen; Rodda, Andrew E.; Simpson, M. Cather
Abstract: Fast, accurate cutting of technical ceramics is a significant technological challenge because of these materials' typical high mechanical strength and thermal resistance. Femtosecond pulsed lasers offer significant promise for meeting this challenge. Femtosecond pulses can machine nearly any material with small kerf and little to no collateral damage to the surrounding material. The main drawback to femtosecond laser machining of ceramics is slow processing speed. In this work we report on the improvement of femtosecond laser cutting of sintered alumina substrates through optimisation of laser processing parameters. The femtosecond laser ablation thresholds for sintered alumina were measured using the diagonal scan method. Incubation effects were found to fit a defect accumulation model, with F th, 1 =6.0 J/cm 2 (±0.3) and F th, ∞ =2.5 J/cm 2 (±0.2). The focal length and depth, laser power, number of passes, and material translation speed were optimised for ablation speed and high quality. Optimal conditions of 500 mW power, 100 mm focal length, 2000 µm/s material translation speed, with 14 passes, produced complete cutting of the alumina substrate at an overall processing speed of 143 µm/s – more than 4 times faster than the maximum reported overall processing speed previously achieved by Wang et al.[1] . This process significantly increases processing speeds of alumina substrates, thereby reducing costs, making femtosecond laser machining a more viable option for industrial users. Highlights: The fs laser ablation threshold of alumina was measured using the D-scan method. The focal length and depth, power, speed, and number of passes were optimised. The optimal conditions allowed complete cutting at an overall processing speed of 143 µm/s. This overall processing speed is more than 4 times faster than previously achieved using fs laser ablation.